Assessing the Potential Risk of Invasion of the Neophyte Pluchea ovalis (Pers.) DC. (Asteraceae) in the Canarian Archipelago Using an Ensemble of Species Distribution Modelling - Juan José García-Alvarado; Miguel Pestano-González; Cristina González-Montelongo; Agustín Naranjo-Cigala; José Ramón Arévalo (Diversity)
Invasive species represent a significant threat to biodiversity and ecosystem conservation, with their impacts often amplified in island ecosystems. Species distribution models (SDMs) can infer the potential habitat throughout the life of an organism and are considered a valuable tool for predicting the risk of expansion of invasive plants and animals. In our approach, we used an ensemble of four presence–absence models (GLM, GAM, Random Forest, and BART) calibrated only with data collected in Tenerife, the island with the best representation of the species, to infer the habitat suitability for Pluchea ovalis (Pers.) DC. (Asteraceae). Subsequently, we transferred the ensembled model to the rest of the Canarian Island archipelago. Our results show that under near-present conditions, the suitable areas are in the coastal and mid-elevations of the south slope sectors of Tenerife and Gran Canarian Islands, as well as a vast portion of the westernmost and drier islands, always coinciding with ravines and highly disturbed ecosystems. In addition, we forecasted the potential distribution of Pluchea ovalis under different climate change conditions (SSP126, SSP370, and SSP585), showing how its habitability would increase in the worst scenarios. Both contexts favor areas gained by the species in places where they are currently not present, revealing new suitable sectors in the westernmost islands.